INNOVATIVE TEACHING STRATEGIES IN IMPROVING RESEARCH COMPETENCE OF PTS STUDENTS IN RESEARCH METHODS COURSE - Bukhori, Mohammad (Abjadia : International Journal of Education, 2024)
Higher education is required to produce graduates with superior research competence to face challenges in the academic and professional world. This study aims to explore innovative teaching strategies in improving the research competence of private university students in the Research Methods course. The research method used is a qualitative approach with a case study design in several private universities in Indonesia. Data collection techniques included in-depth interviews with lecturers and students, classroom observations, and analysis of relevant academic documents. The data were analyzed using a thematic approach to identify the patterns and effectiveness of the teaching strategies applied. The results showed that the implementation of project-based learning strategies, flipped classroom, and the use of digital technology such as data analysis software significantly improved students' research competencies. Students showed improvement in their understanding of research methodology, data analysis skills, and skills in preparing and presenting research reports. This study involved 71 students at one of the PTS that was the subject of the research. The implications of this study emphasize the importance of adapting more interactive and technology-based teaching strategies to support students' research competencies.